Documents and data sharing : the advanced iOS 6 developer's cookbook - Sadun, Erica (Developer's library., 2012)
Under iOS, applications can share information and data as well as move control from one application to another using a variety of system features. Each application has access to a common system pasteboard that allows copying and pasting across apps. Users can transfer documents from one app to another app that supports that format. They can request a number of system-supplied "actions" to apply to a document, such as printing, tweeting, or posting to a Facebook wall. Apps can declare custom URL schemes that can be embedded in text and web pages. This eBook by bestselling author and developer Erica Sadun introduces the ways you can integrate documents and data sharing between applications. You'll see how to add these features into your applications and use them smartly to make your app a cooperative citizen of the iOS ecosystem. This digital short is an adapted excerpt from The Advanced iOS 6 Developer's Cookbook (Early Edition), 4th Edition (ISBN 9780133362534). The content of this digital short may differ slightly from the content in the book. Purchasers of this digital short are invited to use coupon code sadundocdata, good for 30% off the list price of the book on InformIT exclusively.